Investigating Influences on the Pb Pseudo‐Isochron Using Three‐Dimensional Mantle Convection Models With a Continental Reservoir. (16th August 2022) - Panton, James; Davies, J. Huw; Elliott, Tim; Andersen, Morten; Porcelli, Don; Price, Matthew G.
Abstract: For mid‐ocean ridge basalts and ocean island basalts, measurements of Pb isotope ratios show broad linear correlations with a certain degree of scatter. In 207 Pb/ 204 Pb— 206 Pb/ 204 Pb space, the best fit line defines a pseudo‐isochron age ( τ Pb ) of ∼1.9 Gyr. Previous modeling suggests a relative change in the behaviors of U and Pb between 2.25 and 2.5 Ga, resulting in net recycling of HIMU (high U/Pb) material in the latter part of Earth's history, to explain the observed τ Pb . However, simulations in which fractionation is controlled by a single set of partition coefficients throughout the model runs fail to reproduce τ Pb and the observed scatter in Pb isotope ratios. We build on these models with 3D mantle convection simulations including parameterizations for melting, U recycling from the continents and preferential removal of Pb from subducted oceanic crust. We find that both U recycling after the great oxygenation event and Pb extraction after the onset of plate tectonics, are required in order to fit the observed gradient and scatter of both the 207 Pb/ 204 Pb— 206 Pb/ 204 Pb and 208 Pb/ 204 Pb— 206 Pb/ 204 Pb arrays. Unlike much previous work, our model does not require accumulations of subducted oceanic crust to persist at the core‐mantle boundary for long periods of time in order to match geochemical observations. Plain Language Summary: Lead isotope ratios measured within volcanic rocks which originate from deep within Earth (the mantle) define characteristic ages, which geodynamic modelers have previously explained by a global change in the relative behavior of uranium, thorium and lead at some time 2.25–2.5 billion years ago. A shortfall of previous modeling is that it fails to represent all of the different processes which can separate the elements of interest. As well as melting, our simulations feature methods for modeling non magmatic processes which ultimately alter Pb isotope ratios. These are the transportation of U from the continents into the mantle and the preferential loss of Pb from oceanic crust as it descends into the mantle (subduction). We find that a combination of these processes are required to best reproduce the range of Pb isotope ratios measured in rocks from mid‐ocean ridges. Contrary to previous work, we do not require subducted oceanic crust to accumulate in large piles at the base of the mantle. Key Points: We present numerical geodynamic models with new parameterizations for U recycling and preferential Pb removal from subducted oceanic crust A combination of these processes provides a good fit to both Pb pseudo‐isochron and observed scatter of Pb isotope ratios measured in oceanic basalts Our models do not require long term accumulation of subducted oceanic crust to fit geochemical constraints